2017
DOI: 10.1128/jb.00828-16
|View full text |Cite
|
Sign up to set email alerts
|

VfrB Is a Key Activator of the Staphylococcus aureus SaeRS Two-Component System

Abstract: In previous studies, we identified the fatty acid kinase virulence factor regulator B (VfrB) as a potent regulator of ␣-hemolysin and other virulence factors in Staphylococcus aureus. In this study, we demonstrated that VfrB is a positive activator of the SaeRS two-component regulatory system. Analysis of vfrB, saeR, and saeS mutant strains revealed that VfrB functions in the same pathway as SaeRS. At the transcriptional level, the promoter activities of SaeRS class I (coa) and class II (hla) target genes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 57 publications
4
46
0
Order By: Relevance
“…We also provide evidence supporting the FakA-dependent activity of CcpA, as shown through the altered transcription of gltA observed in the fakA mutant. It should be noted that we have recently reported that FakA is an activator of the SaeRS two-component system (30), while another group demonstrated that CodY binds to the sae P1 promoter (39). Thus, it was reasonable to postulate that Sae would be important for the growth phenotype observed in the fakA mutant.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We also provide evidence supporting the FakA-dependent activity of CcpA, as shown through the altered transcription of gltA observed in the fakA mutant. It should be noted that we have recently reported that FakA is an activator of the SaeRS two-component system (30), while another group demonstrated that CodY binds to the sae P1 promoter (39). Thus, it was reasonable to postulate that Sae would be important for the growth phenotype observed in the fakA mutant.…”
Section: Discussionmentioning
confidence: 91%
“…The resulting PCR fragment was digested with EcoRI and SalI and ligated into the same sites of pJB185 to produce pZD3. ␤-Galactosidase activity was determined as previously described (30). Briefly, 1 ml of bacterial culture was collected after 3 or 6 h of growth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our data demonstrate that FakA is needed to induce farE in response to linoleic acid, paradoxically, USA300 ΔfakA exhibited an elevated basal level of farE expression sufficient to promote increased resistance to linoleic acid. This may be due to the pleiotropic phenotype ascribed to USA300 ΔfakA, including an elevated pool of nonesterified fatty acids, leading to reduced transcription of the SaeRS two-component regulator and defective production of Hla toxin (32)(33)(34). Broader metabolic changes were also noted, including altered carbon and amino acid metabolism (35).…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide analysis showed that FA kinase-null strains were specifically deficient in the expression of all virulence factors controlled by the SaeRS system ( 29 ). The fact that acetyl-phosphates are known to phosphorylate response regulators suggests that FA kinase may participate in the regulatory phosphorylation cascade in the SaeRS system ( 29 , 37 ). Although it is clear that transcription of the SaeRS virulence regulon is supported by a functional FA kinase, the connection between FA kinase and SaeRS has not been established.…”
Section: Introductionmentioning
confidence: 99%